Hypokalaemia and outcomes in older patients hospitalized for heart failure - Miroslava Valentova; Samir Patel; Phillip H. Lam; Charles Faselis; Cherinne Arundel; Gregg C. Fonarow; Yan Cheng; Richard M. Allman; Stephan vonHaehling; Stefan D. Anker; Ali Ahmed (ESC Heart Failure)
Abstract Aims Hypokalaemia is a risk factor for ventricular arrhythmias and sudden death in ambulatory patients with chronic heart failure (HF). The objective of this study was to examine the association between hypokalaemia and outcomes in hospitalized patients with decompensated HF in whom sudden death is less common. Methods and results Of the 5881 hospitalized patients with HF, 1052 had consistent hypokalaemia (both admission and discharge serum potassium <4.0 mmol/L), and 2538 had consistent normokalaemia (both admission and discharge serum potassium 4.0–5.0 mmol/L). Propensity scores for consistent hypokalaemia, estimated for each of 3590 (1052 + 2538) patients, were used to assemble a matched cohort of 971 pairs of patients with consistent hypokalaemia vs. consistent normokalaemia, balanced on 54 baseline characteristics (mean age, 75 years; 60% women; 28% African American). We repeated the above process to assemble 2327 pairs of patients with discharge potassium <4.0 vs. 4.0–5.0 mmol/L and 449 pairs of patients with discharge serum potassium <3.5 vs. 4.0–5.0 mmol/L. Hazard ratios (HR) and 95% confidence intervals (CIs) associated with hypokalaemia were estimated in matched cohorts. 30 day all‐cause mortality occurred in 5% and 4% of patients with consistent normokalaemia vs. consistent hypokalaemia, respectively (HR, 0.78; 95% CI, 0.52–1.18; P = 0.241). HRs (95% CI) for 30 day mortality associated with discharge serum potassium <4.0 and <3.5 mmol/L were 0.90 (0.70–1.16; P = 0.419) and 1.69 (0.94–3.04; P = 0.078), respectively. Hypokalaemia (<4.0 or <3.5 mmol/L) had no association with long‐term mortality or other outcomes. Conclusions In hospitalized older patients with HF, compared with normokalaemia (serum potassium 4.0–5.0 mmol/L), hypokalaemia (<4.0 or <3.5 mmol/L) had no significant associations with outcomes.